ØªØÙ„ÙŠÙ„ ØµØ¹ÙˆØ¨Ø© ÙÙŠ ØªØ¹Ù„Ù… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¹Ù†Ø¯ ØªØ®ØµØµ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ahmad Mufarih Hasan Fadly; Muhammad Sofwanudin (Institut Agama Islam Darusssalam Blokagung, 2021)
purpose of this study is to find out what problems or difficulties are experienced in learning Arabic in the Darussalam Arab Generation Language Course (GARD) and how to overcome these difficulties. The type of research used is descriptive qualitative research conducted with three data collection techniques, namely interviews, observation and documentation. The research results obtained are that the ability to speak Arabic in the Darussalam Arab Generation Language Course (GARD) can be increased if course participants are aware of the need to speak Arabic